Peran Guru PAI dalam Membentuk Karakter Religius Siswa - Muh Yusuf; Rizal Awaludin; Eko Nursalim (STIT Syekh Muhammad Nafis Tabalong, 2022)
This research is motivated by the influence of globalisation so that the lack of religious character in public elementary schools. One of the formal education institutions that hold religious character cultivation activities is public elementary school 011, North Sangatta sub-district, East Kutai district. This research method is qualitative field with data collection techniques in the form of observation and interviews. Character cultivation has an important meaning in the field of education, especially in relation to religious character. Therefore, this article aims to explore the impact of Islamic Religious Education (PAI) teachers in shaping students' religious character. This research uses a qualitative approach, focusing on understanding the distinctive features of the phenomenon, including causes, effects, relationships, and all intrinsic factors. The article explores how the role of Islamic Education teachers in shaping students' religious character is exemplified through the exemplary work of the teachers themselves and the implementation of habituation programmes at school, which contribute to the development of strong religious values among students.